PERANCANGAN WEBSITE PENDAFTARAN PESERTA DIDIK BARU PADA SMA KRISTEN YUSUF - Catherine; Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Nowadays, in the digital era, SMA Kristen Yusuf faces challenges in the registration process of new students which is still done manually via telephone, WhatsApp, and direct visits to the school, which hampers the efficiency and accuracy of data. This research aims to design and implement a website-based new student registration system that can simplify the online registration process and improve the efficiency of data management at school. The design of the user interface is done using Figma software, which allows better visualisation and responsiveness to make it easier for users to access the system. Using the Agile method, this system is built with Next.js framework for user interface, MySQL for database management, and Golang for backend data management. The results show that this online registration system makes it easier for parents to register their children and helps the school in managing new student data more efficiently and accurately, as well as increasing the school's visibility in cyberspace, making it easier for prospective students to access.